Analysis of Graves’ disease from the origins to the current historical evolution: The history of Graves’ disease discovery and treatment - Mortara, Lorenzo; Coco, Grace; Gatti, Lucrezia; Piantanida, Eliana; Gallo, Daniela (Medicina Historica, 2022)
Graves’ disease (GD), also called Basedow’s disease, owe the names respectively to the Irish physician Robert James Graves, who described the disease in 1835, and to Karl Adolph von Basedow, who reported the same clinical picture in Germany in 1840. Indeed, it was the Englishman Caleb Hillier Parry to firstly report a case of hyperthyroidism and goiter in 1786, but his report was not published until 1825. Earlier, in 1802, the Italian physician Giuseppe Flajani, described a disease characterized by the coexistence of palpitations and exophthalmos. Graves’ disease is an autoimmune, organ-specific, disorder sustained by auto-antibodies stimulating the thyroid-stimulating hormone (TSH) receptor (R). It is believed that the interaction between susceptible genes and environmental/endogen factor triggers the development of the disease. As a consequence of TSH-R improper stimulation, hyperthyroidism and goiter are the main clinical manifestation of the disease, accompanied, in the 25% of cases, by Graves’ orbitopathy (GO). GD is primarily diagnosed by demonstrating the presence of thyrotoxicosis and the pathognomonic TSH-R antibodies (TSH-RAb). In this manuscript we will refer to the disease as Graves’ disease.